Dirichlet polyhedra for simplex groups of spherical, Euclidean or hyperbolic spaces - Ushijima, Akira (Annales Fennici Mathematici, 2021)
Komori and Umemoto detected combinatorial shapes of Dirichlet polyhedra for simplex groups acting on hyperbolic space. We generalize their result to simplex groups acting on Euclidean or spherical spaces.